Dampak Larangan Ekspor Crude Palm Oil terhadap Pendapatan Petani Kelapa Sawit di Desa Danau Embat, Kecamatan Maro Sebo Ilir - Sri Harimurti; Firna Varina; Ratna Dewi; Bangun Joko Laksono; Dina Yuliasty Lamefa (Pusat riset dan Inovasi Nasional, 2025)
The purpose of the study was to analyze the impact of the crude palm oil export ban on the income of oil palm farming businesses in Danau Embat Village, Maro Sebo Ilir District. The study was conducted from January 2023 to August 2023. The types of data used were primary data and secondary data. The sample determination was carried out by simple random sampling. Data analysis was carried out qualitatively and quantitatively. Quantitative analysis was carried out using the Paired Sample t Test (Test of two paired average differences). The results of the analysis of the two average differences test were significant for oil palm farming business income between before and after the CPO export ban, this can be seen from the significant value of 0.001 which is smaller than the probability value (α) of 0.05, which means that the impact of the CPO export ban has an effect on the decline in the income of oil palm farming businesses on smallholder plantations in Danau Embat Village. The CPO export ban should be reviewed because it will have an impact on the income of oil palm farmers.